Asymptotic and hybrid methods in electromagnetics - Molinet, Frédéric; Andronov, I. V. (Ivan V.); Bouché, Daniel 1958- (Institution of Engineering and Technology, 2005)
The book reviews developments in the following fields: asymptotic theory; electromagnetic creeping waves; hybrid diffraction coefficients; and asymptotic currents.